Respostas
respondido por:
25
343 = 7³
√7 = 7 elevado a 1/2
* 1/2 · x (que já tava elevado) = x/2
7 elevado a x/2 = 7³
* Quando as bases sao iguais, podemos igualar os expoentes também
x/2 = 3
* Extremos por meios.
x = 6
√7 = 7 elevado a 1/2
* 1/2 · x (que já tava elevado) = x/2
7 elevado a x/2 = 7³
* Quando as bases sao iguais, podemos igualar os expoentes também
x/2 = 3
* Extremos por meios.
x = 6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás